2023
DOI: 10.1021/acs.est.3c04155
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Ship Emissions on Air Quality in Southern China: Opportunistic Insights from the Abrupt Emission Changes in Early 2020

Xu Feng,
Yaping Ma,
Haipeng Lin
et al.

Abstract: In early 2020, two unique events perturbed ship emissions of pollutants around Southern China, proffering insights into the impacts of ship emissions on regional air quality: the decline of ship activities due to COVID-19 and the global enforcement of low-sulfur (<0.5%) fuel oil for ships. In January and February 2020, estimated ship emissions of NO x , SO 2 , and primary PM 2.5 over Southern China dropped by 19, 71, and 58%, respectively, relative to the same period in 2019. The decline of ship NO x emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Different trace elements in PM 1 can be used as tracers of pollution sources [91]. Previous studies have shown that As was a tracer element for coal combustion sources, Cr was a tracer element for industrial sources, and V was a tracer element for ship sources [9,37,53,70,91,92]. The relative contribution of each pollution source to SO 2 during the observation period was explored, and the multi-linear regression model was as follows:…”
Section: Impact Of Ship Emissions On Coastal Somentioning
confidence: 99%
See 2 more Smart Citations
“…Different trace elements in PM 1 can be used as tracers of pollution sources [91]. Previous studies have shown that As was a tracer element for coal combustion sources, Cr was a tracer element for industrial sources, and V was a tracer element for ship sources [9,37,53,70,91,92]. The relative contribution of each pollution source to SO 2 during the observation period was explored, and the multi-linear regression model was as follows:…”
Section: Impact Of Ship Emissions On Coastal Somentioning
confidence: 99%
“…To reduce the impact of air pollution emissions from ships on the air quality of coastal cities, a series of policies have been introduced at home and abroad [9][10][11][12][13][14][15][16]. On 1 January 2016, the Ministry of Transport of China (MOT) determined the Beijing-Tianjin-Hebei region (BTH), the Yangtze River Delta (YRD), and the Pearl River Delta (PRD) as domestic emission control areas (DECA 1.0).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation